RADIOTHERAPY EFFECT ON COMPLETE BLOOD COUNT PARAMETER IN PATIENTS WITH NASOPHARYNGEAL CARCINOMA - Achmad Chusnu Romdhoni; Firas Farisi Alkaff; Mega Kahdina; Melinda Masturina; Ristra Ramadhani (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: Nasopharyngeal carcinoma (NPC) is the most common malignant tumor of the nasopharynx. Radiotherapy is a therapy of choice for NPC that has been recognized for a long time and used in various centers of the world. However, radiotherapy is known to still have an adverse effect. It is common practice to evaluate Complete Blood Count (CBC) before, during, and after radiotherapy. However, there has been no study regarding the effect of radiotherapy on all CBC parameters. This study aims to analyze the effect of radiotherapy on CBC in NPC patients before and after radiotherapy treatment. Material and methods: This study was an observational study using secondary data from medical records at the radiotherapy outpatient clinic at Dr. Soetomo General Hospital Surabaya. The subject of this study was patients with NPC who underwent a full cycle of radiotherapy treatment on radiotherapy outpatient clinic in 2016. Patients with incomplete medical records and did not finish the radiotherapy treatment were excluded. A paired T-test and Wilcoxon signed-rank test were used for statistical analysis. Results: There were 105 patients included in this study. Mean Corpuscular Hemoglobin Concentration (MCHC), total leucocyte, lymphocyte, and thrombocyte was significantly decreased after a full cycle of radiotherapy (all p <0.05). Eosinophil, basophil, neutrophil, monocyte, Neutrophil to Lymphocyte ratio (NLR), and Platelet to Lymphocyte ratio (PLR) was significantly increased after a full cycle of radiotherapy (all p <0.05). Conclusion: Radiotherapy had a significant effect on the CBC parameter in NPC patients.